US ECONOMIC ANNOUNCEMENTS: DO THEY CONVEY INFORMATION TO THE AUSTRALIAN SHARE MARKET? - Hyland, Ian; Chinnery, Sean; Evans, John (The journal of contemporary issues in business and government, 2006)
This study covers the period from January 2000 to June 2005 and examines the 'announcement effect' of economic news releases in the United States (US) on returns in the Australian share market. Using previously developed models and professional surveys as proxies for expected components of the announcements, the study analyses how the Australian market reacts to both expected and unexpected components. Three types of US economic announcements are analysed in this study, namely discount rate changes, inflation and real economic activity. Results show that significant relationships occur for each of the three types of economic announcements. These findings provide empirical proof that Australian investors regard US economic news as containing information relevant in the pricing of Australian equities. This has consequences for investors and fund managers throughout Australia who need to consider the impact of US and global economic conditions when developing investment strategies.